2020
DOI: 10.21608/ajar.2020.126645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of puff drying on seedless grape fruits quality criteria compared to convective air drying

Abstract: The goal of the present study is to investigate the effect of explosion puffing and convection air drying on the physical, chemical and sensory properties of dried seedless grape, and cost of operation. The obtained results showed that, the drying rate of puff drying method (PD) was faster than that of convection air drying method at the corresponding drying condition of (60°C and 1.5 m/s air velocity). The seedless grape samples dried by PD were the best for the most of physico-chemical quality properties suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The drying rate is reduced with increased drying time and decreased moisture percent. These outcomes concurred with the findings of [44] for prickly pear pee and [20] for grape, carrot, and okra. According to the results, the best moisture ratio is TD from SD (Figure 5).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The drying rate is reduced with increased drying time and decreased moisture percent. These outcomes concurred with the findings of [44] for prickly pear pee and [20] for grape, carrot, and okra. According to the results, the best moisture ratio is TD from SD (Figure 5).…”
Section: Resultssupporting
confidence: 88%
“…Alphonce and colleagues, on the other hand, showed in their study [16] that consumers are most influenced by the flavor of dried fruits and their credibility attributes, such as organic and fair trade, for which consumers are willing to pay a higher price. The researchers have discussed various drying techniques typically employed in drying fruits [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The drying process was stopped when the moisture content reached approximately 0.04 g/g dry weight (DW) because this moisture content assured that dried avocado could be ground to powder. The drying rate (g/g DW) was computed from Equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the above-mentioned drying processes, RW TM drying was addressed in fewer publications; however, the RW TM drying results were substantially more outstanding. In the literature, the RW TM drying was reported to produce good nutritional and sensory quality of dried fruits and vegetables such as carrots, strawberries [Nindo & Tang, 2007], tomatoes [Abul-Fadl & Ghanem, 2011], mango pulp [Caparino et al, 2012], pomegranate leather [Tontul & Topuz, 2017], cornelian cherry pulp [Tontul et al, 2018], low-fat avocado paste [Da Silva & Da Silva, 2018], apple slices [Rajoriya et al, 2019], goldenberry pulp [Puente et al, 2020], etc. Besides, the RW TM drying was more thermally efficient than convective and freeze-drying [Nindo & Tang, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that solubility is significantly reduced by denaturation of proteins at elevated temperature levels like 110°C under both atmospheric and vacuum conditions, the solubilities of corresponding samples are still higher than the control groups' (p ≤ .05) (Table 3). The literature reported that an increase in the drying temperature adversely affected the solubility values of tomato powder and decreased it (Abul-Fadl & Ghanem, 2011). In another study, the results indicated that the solubility of kefir powder was not changed with a temperature increase during the drying process (Tontul et al, 2021).…”
Section: Techno-physical Properties Of Tarhana Powdersmentioning
confidence: 92%